Development of hybrid strength brick containing bottom ash / Anuar Abdul Wahab - Abdul Wahab, Anuar (2019)
The field of construction is now expanding widely. Hence, the use of a variety of building materials has greatly increased. One of the building materials involved was brick. Brick consists of a variety of brick commonly used in the construction industry. Sand cement brick was not the main focus of this study. This brick used sand as the main materials for production. This condition causes dependence on the use of materials such as a sand increase in the construction industry. Therefore, an innovation study in producing a new brick known as Hybrid Strength Brick (HSB) is to reduce the dependence of this sand. HSB is a new type and concept brick by three layers with two different strength grades and different materials. It was found that the dependence on sand caused a wide range of alarming environmental problems.